Association of lameness with per cent body weight distribution and shifting to individual limbs of static Karan Fries crossbred cows - Singh, Man; Lathwal, S S; Singh, Yajuvendra; Kumar, Anil; Gupta, A K; Mohanty, T K; Raja, T V; Gupta, R K; Sharma, V; Chandra, G; Kumar, M (The Indian Journal of Animal Sciences, 2012)
Lameness in crossbred cows causes considerable economic loss hence efforts were made to develop effective automated technique to diagnose it at an earlier stage. Lactating Karan Fries crossbred cows (148) were assigned the appropriate lameness score (VLS). Total body weight and body weight distributed to individual limbs were recorded. Data were analyzed to access the effect of pregnancy, stage of lactation and parity on body weight distribution. Stage of pregnancy had significant effect on total body weight as well body weight distributed to right hind and left hind limbs. Total body weight and body weight distributed to all the 4 limbs was the highest during third trimester of pregnancy. Stage of lactation significantly affected total body weight which was highest during late lactation. Total body weight and weight distributed to right front and right hind legs were significantly higher for cows in fourth or above parity. Per cent distribution of body weight to individual limbs of cows suffering from various categories of lameness was significantly different from one another. Percentage distribution of total body weight on front and rear half of no lame cows was observed in a ratio of 26:21 while for right and left half it was 53:43. The pattern of front to rear and right to left distribution of per cent body weight of cows under various categories of lameness was similar. Shifting of per cent body weight to right and left hind limbs was significant. Lame cows reflected both contra lateral as well as diagonal weight shifting; moreover cows lame with hind limbs shifted their weight to their front limbs also.